Nurses and midwives perceptions of missed nursing care – A South Australian study. Issue 4 (December 2015) - Verrall, Claire; Abery, Elizabeth; Harvey, Clare; Henderson, Julie; Willis, Eileen; Hamilton, Patti; Toffoli, Luisa; Blackman, Ian
Summary: Background: Budgetary restrictions and shorter hospital admission times have increased demands upon nursing time leading to nurses missing or rationing care. Previous research studies involving perceptions of missed care have predominantly occurred outside of Australia. This paper reports findings from the first South Australian study to explore missed nursing care. Aim: To determine and explore nurses' perceptions of reasons for missed care within the South Australian context and across a variety of healthcare settings. Method: The survey was a collaborative venture between the Flinders University of South Australia, After Hours Nurse Staffing Work Intensity and Quality of Care project team and the Australian Nursing and Midwifery Federation, SA Branch. Electronic invitations using Survey Monkey were sent to randomly selected nurses and midwives and available online for two months. Three hundred and fifty-four nurses and midwives responded. This paper reports qualitative data from answers to the open questions. Findings: Three main reasons for missed care were determined as: competing demands that reduce time for patient care; ineffective methods for determining staffing levels; and skill mix including inadequate staff numbers. These broad issues represented participants' perceptions of missed care. Conclusion: Issues around staffing levels, skill mix and the ability to predict workload play a major role in the delivery of care. This study identified the increasing work demands on nurses/midwifes. Solutions to the rationing of care need further exploration.